Experimental Methods in Chemical Engineering: Mass Spectrometry—MS. (9th April 2019) - Perreault, Patrice; Robert, Etienne; Patience, Gregory S.
Abstract: Mass spectrometry identifies the atomic mass of molecules and fragments in the gas phase. The spectrometer ionizes the molecules that then pass through an electric or magnetic field towards a detector. The field modifies the molecule's trajectory and we infer mass from its direction and velocity in a static field or from the stability of its path in a dynamic field. The electric current is amplified and a mass spectrum is generated from the location or timing of the signal from the detector, translated into a plot of the intensity as a function of the mass‐over‐charge ratio. It is field deployable, measures concentrations in real time with a temporal resolution better than 100 ms, and detection limits of fg. However, the signal drifts with time so we have to calibrate it as frequently as every hour. Calibrating requires multiple mixtures with varying concentrations to map the non‐linear response. The Web of Science Core Collection indexed over 60 000 articles that refer to MS (2016 and 2017) with applications ranging from permanent gas analysis, to identifying protein, forensic science, and natural products. The bibliometric software VOSViewer(2010 ) identified four clusters of research related to MS: (1) proteomics, proteins, plasma, and metabolomics; (2) solid phase extraction together with gas chromatography; (3) tandem mass spectrometry and liquid chromatography; and (4) waste water and toxicity. We expect that the technique will continue to evolve with increased sensitivity, lower drift, and greater specificity. Miniaturization efforts should also continue in order to develop faster field deployable instruments.